Relationship between pediatric asthma and respiratory microbiota, intestinal microbiota: a narrative review - Liu, Lian; Zhao, Wenqi; Zhang, Han; Shang, Yunxiao; Huang, Wanjie; Cheng, Qi (Frontiers in Microbiology, 2025)
Pediatric asthma is a common chronic airway inflammatory disease that begins in childhood and its impact persists throughout all age stages of patients. With the continuous progress of detection technologies, numerous studies have firmly demonstrated that gut microbiota and respiratory microbiota are closely related to the occurrence and development of asthma, and related research is increasing day by day. This article elaborates in detail on the characteristics, composition of normal gut microbiota and lung microbiota at different ages and in different sites, as well as the connection of the gut—lung axis. Subsequently, it deeply analyzes various factors influencing microbiota colonization, including host factor, delivery mode, maternal dietary and infant feeding patterns, environmental microbial exposure and pollutants, and the use of antibiotics in early life. These factors are highly likely to play a crucial role in the onset process and disease progression of asthma. Research shows that obvious changes have occurred in the respiratory and gut microbiota of asthma patients, and these microbiomes exhibit different characteristics according to the phenotypes and endotypes of asthma. Finally, the article summarizes the microbiota—related treatment approaches for asthma carried out in recent years, including the application of probiotics, nutritional interventions, and fecal microbiota transplantation. These treatment modalities are expected to become new directions for future asthma treatment and bring new hope for solving the problem of childhood asthma.